ANTARES constrains a blazar origin of two IceCube PeV neutrino events - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astronomy & Astrophysics, 2015)
Results. Both blazars predicted to be the most neutrino-bright in the TANAMI sample (1653-329 and 1714-336) have a signal flux fitted by the likelihood analysis corresponding to approximately one event. This observation is consistent with the blazar-origin hypothesis of the IceCube event IC 14 for a broad range of blazar spectra, although an atmospheric origin cannot be excluded. No ANTARES events are observed from any of the other four blazars, including the three associated with IceCube event IC20. This excludes at a 90% confidence level the possibility that this event was produced by these blazars unless the neutrino spectrum is flatter than -2.4.
Keywords: neutrinos; galaxies: active; quasars: general